Exploring The Effects of Creativity and Educational Support on Digital Entrepreneurial Intention - Muhamad Ridwan; Ahmad Zaki; Alvian Alvin Mubarok; Rolan Mart Sasongko; Budi Purnomo Saputro (Jurnal Ilmu Administrasi dan Bisnis, 2024)
This study examines the influence of creativity and educational support on digital entrepreneurial intentions among Indonesian students. Data was collected through an online survey involving 303 respondents, using a 5-point Likert scale to measure relevant variables. The analysis was conducted using the Partial Least Square - Structural Equation Modelling (PLS-SEM) approach with SmartPLS 3.0. The results show that creativity and educational support significantly influence digital entrepreneurial intentions. Creativity plays a key role in identifying business opportunities, while educational support enhances entrepreneurial skills. This study emphasizes the importance of integrating entrepreneurship education into academic curricula to address the high unemployment rates among university graduates in Indonesia. Adequate support from educational institutions in the form of incubation centers and seed funding is strongly recommended to facilitate the development of digital entrepreneurship among students. This research contributes to theoretical understanding and provides practical implications for entrepreneurship education in the digital era.